(3QSGdI aj GdLhGH Yf eSGFd gfOSjIs - (3efUhQ Hf Ydj, CHh fUQ GHf YQGb , J fMh (B425 (3g`s
(3ChdgG (B:s
(3hUdJ GdeSGFd GdJi bQfJgG HcJGHc hPcQJ Gf KdGKG efgG bO JVefgG cJGH CHj Sgd Gdchgj ai GdHQcGQ GdJGe s
(3BNQgG (B:s
(3agPg CLhHI GdeSGFd GdJi SCdJ GdCHGfI YfgG Ydi bQH ZhQgG hSghdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B103 (3h (B- (3U(B106 (3hs
(3CLGH HgG Ydi CSFdI CHj QjMGf eMeO Hf CMeO GdHjQhfis
(3GfXQ CjVkG GdHQcGQ GdJGe JMJ Qbe (B23 (3QjGVjGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B861 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjVjGJ (B- (3bSe (B3 - (3U (B48 s
Keywords: (3GdQjGVjGJs